Organizational justice and tolerance to uncertainty of employees - Fofanova, Galina A.; Sorokina, Anastasia A. (Journal of the Belarusian State University. Philosophy and Psychology, 2020)
Employees are one of the organization’s valuable assets. Psychological rather than business characteristics of personnel sometimes play a key role in the success of implementing organizational changes. One of these characteristics is tolerance for uncertainty – a personal quality, which means a desire for change, novelty and originality, a willingness to go the wrong way and prefer more complex tasks, have the ability to be independent and go beyond the accepted limits. At the same time, this parameter is in a certain way connected with the features of assessing the organizational situation, norms and rules of distribution of benefits, managerial decisions organizational justice. The results of an empirical study of the relationship between tolerance and uncertainty of employees and organizational justice are presented in this article.
Keywords: organizational justice; procedural justice; interaction justice; distributive justice; employee uncertainty tolerance; employees; organization leaders; holding company; Belarus